2000
DOI: 10.1128/jvi.74.2.883-891.2000
|View full text |Cite
|
Sign up to set email alerts
|

LMP1 of Epstein-Barr Virus Induces Proliferation of Primary Mouse Embryonic Fibroblasts and Cooperatively Transforms the Cells with a p16-Insensitive CDK4 Oncogene

Abstract: The latent membrane protein LMP1 of Epstein-Barr virus (EBV) is often present in EBV-Epstein-Barr virus (EBV) is a human gammaherpesvirus commonly carried in the majority of the human population. It is the causative agent for proliferative diseases such as infectious mononucleosis and oral hairy leukoplakia in AIDS patients. It is also implicated in a variety of human malignancies that include Burkitt's lymphoma, nasopharyngeal carcinoma, Hodgkin's lymphoma, nasal T-cell lymphoma, and immunoblastic lymphomas i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…We have previously reported that Id1 expression in NPC cells downregulated the Rb/p16 INK4a pathway . This is in agreement to our previous study in rodent fibroblasts, which showed that inactivation of the CDK4/p16 INK4a regulatory pathway was a downstream event of LMP1 (Yang et al, 2000). The p16 INK4a protein regulates cell cycle G1/S entry and is largely responsible for the onset of replicative senescence in human epithelial cells (Ohtani et al, 2001).…”
Section: 1207580 Published Online 5 April 2004supporting
confidence: 81%
See 1 more Smart Citation
“…We have previously reported that Id1 expression in NPC cells downregulated the Rb/p16 INK4a pathway . This is in agreement to our previous study in rodent fibroblasts, which showed that inactivation of the CDK4/p16 INK4a regulatory pathway was a downstream event of LMP1 (Yang et al, 2000). The p16 INK4a protein regulates cell cycle G1/S entry and is largely responsible for the onset of replicative senescence in human epithelial cells (Ohtani et al, 2001).…”
Section: 1207580 Published Online 5 April 2004supporting
confidence: 81%
“…Constitutive expression of LMP1 in NP69 cells was achieved by retroviral expression of an NPC-derived LMP1. The construction of the LMP1 expression vectors had been previously described (Yang et al, 2000). NP69 cells infected with the empty vector, pLNSX, were also established as a negative control.…”
Section: 1207580 Published Online 5 April 2004mentioning
confidence: 99%
“…17,19 Our previous studies in rodent fibroblasts and human nasopharyngeal epithelial cells showed that the Cdk4/p16 regulatory pathway is repressed by the EBV-encoded LMP1 and conferred growth advantage to cells. 20,21 Hypermethylation of the p16 gene has been shown to be a common event in NPC. 18 Loss of heterozygosity of the chromosome 9p at the p16 INK4A locus could be detected in premalignant nasopharyngeal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…We recently observed for the ®rst time that LMP1, as a single EBV gene, is sucient to induce the proliferation of primary mouse ®broblasts (Yang et al, 2000). In this study, we examine the roles and mechanisms of LMP1 in inducing the proliferation of primary cells.…”
Section: Ink4amentioning
confidence: 99%